Rediscovery of Tordylium brachytaenium (Tordylieae, Apioideae, Apiaceae), an endemic and threatened species in Turkey - Doğru-Koca, Aslı; Zare, Golshan (Phytotaxa, 2015)
The threatened endemic species, Tordylium brachytaenium, which was not collected after the first description by Boissier and Heldreich in 1849, was rediscovered. An expanded species description, comments about its distribution, ecology and conservation are presented. Additionally, its distinction from the closely related species in respect of pollen and mericarp morphology is provided. The IUCN assessment of T. brachytaenium is also briefly discussed.